THE TABOO OF SEXUAL RELATIONSHIP IN SASAK CULTURE: A STUDY OF ANTROPOLOGICAL LINGUISTICS: TABU IHWAL HUBUNGAN SEKSUAL DALAM KEBUDAYAAN MASYARAKAT SASAK: KAJIAN LINGUISTIK ANTROPOLOGI - Suliadi Suliadi (LLDIKTI Wilayah X, 2023)
The porpuse of this study was to describe the taboo words within the Sasak people regarding the mention of sexual relations; find certain words that are practiced by the Sasak community as a substitute for taboo words in referring to sexual relations; and explore the cultural meanings of words that are practiced in referring to sexual relations, especially words that considered as avoidance. The method in this study is descriptive qualitative by applying the Miles & Hberman analysis model in the form of data collection, data reduction, data display, and conclusions.The results of this study are (1) there are three words that considered as the taboo by the Sasak people in referring to sexual relations because they are considered vulgar, namely the words mesawa, mengancuq, and mengancot 'having intercourse'; (2) there are several metaphorical words that are practiced as avoidance in referring to sexual relations, such as: the words penganténan 'to make love', lindur 'earthquake', ngaen bangket 'irrigating the rice fields', campur 'mixed', menyopoq 'union', baroq saweq 'just finished ', taek 'up', and nggalѐngin 'afternoon'; And (3) there is prohibition in mentioning sexual relationships with dirty words or vulgar reflect that the Sasak people show the language etiquette, so the words spoken do not make the speakers uncomfortable.